Análise das perspectivas de comércio para o segmento de flores e plantas ornamentais no Brasil - Borba, Vanessa Pinto de (My University, 2021)
As an international standout in the agribusiness sector, Brazil has several segments belonging to this important economic branch, such as the diversified cultivation of flowers and ornamental plants on national soil. This production chain encompasses hundreds of categories and thousands of varieties, with unique needs and vast geographic extension. Characterized by the high demand for labor, largely non-mechanizable, it differs in many aspects from the commodities sector, but in the same way it registers attractive numbers and represents a relevant opportunity for the national economy. The aim of this study is to analyze the perspectives of trade for the segment of Brazilian flowers and ornamental plants, carried out through the inspection of bibliographic papers and enriched by qualitative research applied to organizations in the area. Nationally, there is an extensive consumer market, with demand leveraged by the Covid-19 pandemic. The sector's export flows pointed to the need for improvement in logistical infrastructure and investment in innovation. To achieve the expansion of international supply, it was noted that the sector of flowers and ornamental plants in Brazil needs proximity to the procedures of foreign trade, starting from the reduction of bureaucracy and the more intense action of state agencies in the diversification of the consumer market beyond national borders. Therefore, it was understood that the promotion of a more active export culture, still lacking in Brazil, added to the investment in research and development of more competitive products, together with logistical improvement, enables a promising path for Brazilian flowers and ornamental plants to be able to reach an international level, achieving worldwide admiration and recognition. [resumo fornecido pelo autor]
Destaque internacional no setor de agronegócio, o Brasil possui variados segmentos pertencentes a este importante ramo econômico, a exemplo do diversificado cultivo de flores e plantas ornamentais em solo nacional. Esta cadeia produtiva abrange centenas de categorias e milhares de variedades, com necessidades peculiares e vasta extensão geográfica. Caracterizado pela alta demanda de mão de obra, em grande parte não mecanizável, difere-se em muitos aspectos do setor de commodities, porém de mesma forma registra números atrativos e representa oportunidade relevante para a economia nacional. O alvo do presente estudo consiste na análise das perspectivas do comércio para o segmento de flores e plantas ornamentais brasileiras, efetuada por intermédio da inspeção de obras bibliográficas e enriquecida por pesquisas qualitativas aplicadas a organizações da área. No âmbito nacional, destaca-se extenso mercado consumidor, com demanda alavancada pela pandemia da Covid-19. Os fluxos de exportação do setor apontaram a necessidade de melhoria na infraestrutura logística e investimento em inovação. Para alcançar a expansão de fornecimento internacional, denotou-se que o setor de flores e plantas ornamentais no Brasil necessita de proximidade aos trâmites de comércio internacional, partindo da desburocratização e a atuação mais intensa de órgãos estaduais na diversificação do mercado consumidor além das fronteiras nacionais. Com isso, entendeu-se que o fomento de uma cultura exportadora mais atuante, ainda carente no Brasil, somado ao investimento em pesquisa e desenvolvimento de produtos mais competitivos, conjuntamente com melhoria logística viabiliza um caminho promissor para que as flores e plantas ornamentais brasileiras possam atingir um patamar internacional, alcançando a admiração e o reconhecimento mundiais. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Plantas ornamentais; Agroindústria